Cybersecurity threats, malware trends, and strategies mitigate exploits, malware, phishing, and other social engineering attacks - Rains, Tim (Packt, 2020)
It is challenging for an organization to estimate the effectiveness of a cybersecurity strategy. Cybersecurity Threats, Malware Trends, and Strategies acts as a comprehensive guide to cybersecurity based on thousands of cybersecurity discussions and threat intelligence briefings that the author has participated in over a two-decade career